Novel frameshift mutation in STK33 is associated with asthenozoospermia and multiple morphological abnormalities of the flagella. Issue 21 (21st June 2021) - Ma, Hui; Zhang, Beibei; Khan, Asad; Zhao, Daren; Ma, Ao; Zhou, Jianteng; Khan, Ihsan; Khan, Khalid; Zhang, Huan; Zhang, Yuanwei; Jiang, Xiaohua; Dil, Sobia; et al.
Abstract: Serine/threonine kinases domain-containing proteins are known to play important functions in sperm flagella and male fertility. However, the roles of these proteins in human reproduction remain poorly understood and whether their variants are associated with human asthenozoospermia have not been reported. Here, we recruited a Pakistani family having four infertile patients diagnosed with idiopathic asthenozoospermia without any ciliary-related symptoms. Whole-exome sequencing identified a novel homozygous frameshift mutation (c.1235del, p.T412Kfs * 14) in serine/threonine kinase 33 ( STK33 ), which displays a highly conserved and predominant expression in testis in humans. This variant led to a dramatic reduction of STK33 messenger RNA (mRNA) in the patients. Patients homozygous for the STK33 variant presented reduced sperm motility, frequent morphological abnormalities of sperm flagella and completely disorganized flagellar ultrastructures, which are typical for multiple morphological abnormalities of the flagella (MMAF) phenotypes. Overall, these findings present evidence establishing that STK33 is an MMAF-related gene and provide new insights for understanding the role of serine/threonine kinases domain-containing proteins in human male reproduction.